Computer science experiments - Walker, Pam, 1958-; Wood, Elaine, 1950- (New York, NY : Facts on File, 2010)
Presents 20 new, tested experiments related to the intriguing field of computer science. Most of the experiments utilize Internet-based computer research to teach key science concepts. The experiments are designed to promote interest in science in and out of the classroom, and to improve critical-thinking skills.
Introduction -- Safety precautions -- Bioethics video production -- Coral reef conservation -- Carbon footprint -- Virtual fetal pig dissection -- Conservation of mass -- Astronaut trading cards -- Simple machines -- Hydrolysis and dehydration synthesis -- Using cloud patterns to predict weather -- Create a climatogram -- Mapping lightning strikes -- Human parasites -- Rocks and minerals -- Breathing demonstration -- Nanoscale science -- How are caves formed? -- Sunspots and the solar cycle -- Types of chemical bond -- The history of DDT -- The power of a tsunami --Scope and sequence chart -- Grade level -- Setting -- Our findings.
Includes bibliographical references and index.
6-12.
Keywords: Computer science -- Experiments; Computer science -- Study and teaching (Middle school) -- Activity programs; Computer science -- Study and teaching (Secondary) -- Activity programs; Science -- Study and teaching -- Computer network resources; Internet in education; Science projects